Theorising repeated displacement: The role of anticipation and precedent. The case of Burundi. (January 2023) - Purdeková, Andrea; Birantamije, Gerard
Abstract: What drives mass displacement in the context of cyclical violence and repeated refugee flows? We take the context of Burundi and the Great Lakes region in Africa to show the limitations of available causal models, which are typically focused on war-related displacement, struggle to connect war and post-war displacement and where mass displacement is understood as a response to acute violence. Burundi is an excellent case study to problematise episodic, reactive and war-related causal models of displacement as this is a context with cyclical mass displacements spanning both war and peace and interconnected through dynamics such as people's anticipation of worsening and reading of precedent. Taking the 2015 third-term contestation in Burundi as a starting point, we argue for a longue-durée approach to displacement and for complicating the dominant causality framework by bringing in three dynamics: anticipation, endogeneity and entrenchment. Anticipation considers how longer-term (violent) pasts rather than immediate events inform displacement. In Burundi, people drew on past experiences as well as rumours in an attempt to anticipate a deterioration. Endogeneity questions easy separations between displacement, violence and political crisis and rather sees them as co-constitutive. In Burundi, mass displacement cleared the opposition from domestic space and disenfranchised large populations in subsequent elections. It also drew increased transnational repression and triggered security fears on behalf of the regime. Finally, as the case of Burundi shows, redisplacement does not represent a 'repeat' or replication of past experience, but rather a new form of relation to exile and home. Against a long past of repeated displacements, many Burundians are entrenching in exile.